DOI: 10.22215/etd/2016-11233
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Identification and Characterization of Mafic-Ultramafic Intrusions in Plume Centre Regions

Abstract: Gravity and magnetic data from the EGM2008 and EMAG2 datasets are used for a global study of geophysical anomalies in LIP plume centre regions with the goal of identifying maficultramafic intrusions linked to those LIPs. Geophysical anomalies within eighteen LIPs are investigated. Four of these LIPs are selected for detailed modelling: the Mackenzie, High-Arctic, Kunene-Kibaran, and Deccan LIPs.Modelling supports that these anomalies are produced by large (radius >30 km) and generally deep-seated crustal intru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…An excellent case is the shallow Muskox intrusion on the Canadian Arctic mainland that is a part of the Mackenzie LIP (section 3.1) and its link to one of the deep intrusions to the north identified from gravity data. The other large intrusions that circumscribe the plume centre may have also produced secondary chambers with similar economic potential as the Muskox (Blanchard 2016 We recognize three distinct spatial distribution types for regional-scale layered maficultramafic intrusions within LIP plume centre regions. These are: 1) Intrusions that circumscribe a plume centre (formed as a result of plume-induced uplift and subsequent subsidence), located at 150 -500 km from the plume centre and spaced at regular intervals around the plume centre.…”
Section: Link Between Deep and Shallow Intrusions And Implications Fmentioning
confidence: 69%
See 2 more Smart Citations
“…An excellent case is the shallow Muskox intrusion on the Canadian Arctic mainland that is a part of the Mackenzie LIP (section 3.1) and its link to one of the deep intrusions to the north identified from gravity data. The other large intrusions that circumscribe the plume centre may have also produced secondary chambers with similar economic potential as the Muskox (Blanchard 2016 We recognize three distinct spatial distribution types for regional-scale layered maficultramafic intrusions within LIP plume centre regions. These are: 1) Intrusions that circumscribe a plume centre (formed as a result of plume-induced uplift and subsequent subsidence), located at 150 -500 km from the plume centre and spaced at regular intervals around the plume centre.…”
Section: Link Between Deep and Shallow Intrusions And Implications Fmentioning
confidence: 69%
“…It has been suggested that the gravity anomalies D1, D2 and D3 coincide with minor exposures of alkaline and acidic intrusions (Karanth and Sant 1995;Mishra et al 2001); however it's unclear whether these exposures are components of the main intrusive bodies, or if they are instead shallow intrusions sourced from deeper units. Both scenarios were considered (Blanchard 2016) and the preferred model is presented here.…”
Section: Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…U-Pb age determinations from this intrusion show that emplacement occurred at 92 Ma based on determinations from the gabbroic and microgranite phases Estrada and Henjes-Kunst, 2013). Lastly, on the basis of aeromagnetic and gravity anomalies in the vicinity of Kleybolte Peninsula, extreme northwestern Ellesmere Island, another mafic intrusion has been geophysically identified and interpreted as a part of the HALIP (Blanchard, 2016).…”
Section: Halip Plumbing System and Genesismentioning
confidence: 99%